Post-Covid 19 Amusement Park Satisfaction Attributes - Michael Adiwijaya; Halimin Herjanto; Grace Gutierrez (Universitas Pasundan, 2024)
Despite the rise of Asian theme park visitations, the extant investigation of visitor’s satisfaction in the Asian context is very limited. This study, therefore, examines and discusses the compiled findings of theme park visitors’ satisfaction in Asia, specifically in Indonesia. Based on 440 theme park visitors’ comments and feedback on the TripAdvisor website were read, reviewed, and content analyzed. As a result, the research discovered that in the Indonesian context, visitors’ satisfaction is influenced by ten recurrent themes: physical facilities, restaurant, entertainment, environment, waiting time, price, staff, location, security, and management. Additionally, three new themes: maintenance, booking system, and health protocol are responsible for developing theme park visitors’ satisfaction at theme parks. Limitations and future study avenues are also discussed and presented.